Predatory arthropod community composition in apple orchards: Orchard management, landscape structure and sampling method. (5th October 2020) - Hambäck, Peter A.; Porcel, Mario; Tasin, Marco; Samnegård, Ulrika
Abstract: Studies on predatory arthropods in agricultural areas seldom include Diptera other than hoverflies, partly because common sampling methods are less effective for capturing species that easily fly off when disturbed. To study the effect from this bias when describing the predator community, we compared traditional beat sampling of branches and suction sampling for describing the community of predatory arthropods in Swedish apple orchards, both organic orchards and orchards using integrated pest management (IPM). Our results indicate that the proportion of both predatory dipterans and parasitic hymenopterans increase dramatically when using suction sampling (Diptera: 32% vs. 20%, Hymenoptera: 25% vs. 7%). In fact, predatory dipterans were the most abundant predatory group when using suction sampling, in contrast to beat sampling where spiders were the most abundant group. One group of predatory flies that was particularly rich in both species and individuals in the surveyed apple orchards was dance flies in the family Hybotidae. Even though the bias of sampling method was evident, it was encouraging that the method choice did not affect the conclusions concerning management on predatory arthropod communities. With both methods, dipteran and coleopteran predators were more abundant in organic apple orchards whereas opilionids were more abundant in orchards managed according to IPM. The inclusion of landscape variables further indicated effects of landscape diversity and of deciduous forest cover, but the response varied in sign between predatory groups. Whereas both Coleoptera and Heteroptera were more abundant in orchards surrounded by more complex landscapes (high landscape diversity and/or high deciduous forest cover), spiders, opilionids and dipterans were rather less abundant in these orchards. To conclude, our study points to the potential importance of predatory dipterans in apple orchards, and we highly recommend future studies of arthropod predators in apple and other crops to actively include predatory Diptera.